"A Survey on the Prevalence of Stroke Risk Factors in CVA Diagnosed Patients, Hospitalized in Shahid Beheshti Hospital in 1998 1998." - SA Masoud (Tehran University of Medical Sciences, 2002)
A storke is the sudden onset of focal neurologic deficit from a vascular mechanism and is the 3 rd cause of death in developed countries. This study was carried out to evaluate the known risk factors of stroke and their effect on the onset of it in Shahid Behesti hospital in Kashan in 1998. The descriptive strategy of this study was conducted on 300 patients with CVA, that their illness was documented based on their clinical and CT-Scan findings. The informations about the patients was listed in an information list after hospitalization. Most cases were between 70-80 years old. 64% of cases had hypercholestrolemia, 15% diabetic history, 54% hypertension, 40.6% had positive history of smoking and 22.4 % had combined hyperlipidemia. Considering the high incidence of hypertension, hyperlipidemia and diabetes among the patient with CVA, and the high incidence of smoking as well, more attention is needed to reduce these risk factors in the society.